Bijeenkomst in het kader van Europese Verkiezingen 1979. V.l.n.r. Vondeling, Pronk, Wooldrik - Bogaard, Hans van den (1979)
Bijeenkomst in het kader van Europese Verkiezingen 1979. V.l.n.r. Vondeling, Pronk, Wooldrik.